2017
DOI: 10.1111/jgh.13811
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise application of fibrosis index based on four factors, red cell distribution width–platelet ratio, and aspartate aminotransferase–platelet ratio for compensated hepatitis B fibrosis detection

Abstract: In source-limited settings without transient elastography, stepwise applying FIB-4, RPR, and APRI could free nearly half of CHB patients from liver biopsies in detecting significant fibrosis and cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…A total of 2831 studies were searched by the described search strategies, of which 2627 were excluded following title and abstract screening. Of those, 81 papers were included in the review following full-text screening (Text S5); 47 studies were related to the APRI[24-70], 11 to the ARFI[29,42,69-77], 32 to the FIB-4[24,25,27,30,35,36,39,40,43-46,48-55,57,58,60,62,63,65-69,78-79], 29 to the FibroScan[28,38,42,52,53,58,60,61,71,73,80-98], and 6 to the MRE[99-104].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 2831 studies were searched by the described search strategies, of which 2627 were excluded following title and abstract screening. Of those, 81 papers were included in the review following full-text screening (Text S5); 47 studies were related to the APRI[24-70], 11 to the ARFI[29,42,69-77], 32 to the FIB-4[24,25,27,30,35,36,39,40,43-46,48-55,57,58,60,62,63,65-69,78-79], 29 to the FibroScan[28,38,42,52,53,58,60,61,71,73,80-98], and 6 to the MRE[99-104].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to our findings, Chen et al found, in a Chinese cohort of chronic hepatitis-B fibrosis patients, FIB-4 and APRI scores to be significantly different between patients with cirrhosis and moderate or severe fibrosis, respectively. 29 The discriminatory potential of a certain test might be influenced by the reference test. We and others 28,29 used histological grading as reference standard, while some studies use TE as reference for fibrosis staging.…”
Section: Discussionmentioning
confidence: 99%
“…The discriminatory potential of a certain test might be influenced by the reference test. We and others used histological grading as reference standard, while some studies use TE as reference for fibrosis staging . Deviations in diagnostic accuracy might also occur due to the type of histologically analyzed specimen, whether a needle biopsy or a surgical specimen is examined.…”
Section: Discussionmentioning
confidence: 99%
“…7 Serologic tests and FibroScan have been recommended by the World Health Organization (WHO) as noninvasive tests for CHB patients. 8 However, FibroScan is costly and has been shown to be unfavorable in patients with ascites. 9 Serum markers have been proposed to evaluate liver disease including alanine aminotransferase (ALT), the aspartate aminotransferase (AST)-toplatelet ratio index (APRI), the fibrosis index based on the four factors (FIB-4), the red cell volume distribution width (RDW)-to-platelet ratio (RPR), and the gamma-glutamyl transpeptidase (GGT)-to-platelet ratio (GPR).…”
mentioning
confidence: 99%